The Influence Of Accounting Profit And Cash Flow On Bankruptcy Prediction In Insurance Companies On The Indonesian Stock Exchange - Kurniawan, Andrie; Givan, Bryan; Sovyanty, Devy; Rizkie, Ricky (Jurnal Ekonomi, 2024)
This research investigates the influence of profit and cash flow on bankruptcy prediction in insurance companies listed on the Indonesia Stock Exchange. The research sample is determined through purposive sampling, with inclusion criteria for issuers that have published audited financial reports between 2017 and 2021. The collected data are processed using multiple regression analysis with SPSS 26.00. The research results indicate that profit does not significantly affect bankruptcy prediction in insurance companies. This may be attributed to the distinct characteristics of the insurance industry compared to other sectors, where profit only sometimes reflects the overall financial condition, especially when facing large claims or unpredictable risks. Conversely, cash flow significantly influences bankruptcy prediction in insurance companies. Cash flow is considered a primary indicator to assess a company's ability to meet claim payment obligations and address liquidity issues, particularly in the insurance industry, which frequently faces significant payment obligations. The conclusion of this research provides insights that a better understanding of cash flow dynamics is more relevant in predicting the bankruptcy conditions of insurance companies than profit. Practical implications of this research include emphasizing the importance of risk management, effective capital structure, and special attention to cash flow as a critical factor in maintaining insurance companies' stability and operational continuity.